1970
DOI: 10.21129/nerve.2015.1.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intra-operative Saline Irrigation during Burr Hole Surgery on the Recurrence for Chronic Subdural Hematomas

Abstract: Objective:The aim of this study is to compare the postoperative recurrence rates and alteration in follow-up brain CT radiographic results between patients with chronic subdural hematoma (CSDH) treated by burr hole trephination with or without irrigation during the surgery. Methods: A total of 100 patients diagnosed with CSDH underwent burr hole trephination from January 2013 to May 2015. The patients were divided into two groups: those who underwent intra-operative saline irrigation and those who did not. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Regarding the use of irrigation, Kim et al [1] reported a higher recurrence rate in a 114-case saline irrigation group with closed drainage than in a 38-case non-irrigation group with closed drainage. Conversely, Ishibashi et al [14], Jang et al [8], and Lee et al [5] reported better prognoses after irrigation. The present study also showed that the recurrence rate was significantly lower after intraoperative irrigation.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Regarding the use of irrigation, Kim et al [1] reported a higher recurrence rate in a 114-case saline irrigation group with closed drainage than in a 38-case non-irrigation group with closed drainage. Conversely, Ishibashi et al [14], Jang et al [8], and Lee et al [5] reported better prognoses after irrigation. The present study also showed that the recurrence rate was significantly lower after intraoperative irrigation.…”
Section: Discussionmentioning
confidence: 97%
“…It is usually treated surgically and has low postoperative morbidity and mortality rates. However, its postoperative recurrence rate is high; therefore, the question of how best to treat CSDH remains a meaningful topic in the neurosurgical field [5,19]. Many studies have investigated CSDH recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations